Legal Issues of Government Regulation Number 48 of 2025 on the Utilization of State General Reserve Land - Susilo Lestari (Inovasi Pratama Internasional. Ltd, 2027)
This article examines the legal and practical implications arising from Government Regulation Number 48 of 2025 concerning the Management and Control of Abandoned Areas and Abandoned Land. The Regulation is intended to optimize the utilization of land reserves for the benefit of the State, National Development, and Agrarian Reform. Nevertheless, its implementation has generated critical issues relating to legal certainty, the protection of land ownership rights, and inconsistencies within the existing agrarian legal framework. Employing a normative juridical approach, this study analyzes the contradictions between statutory provisions and their enforcement in practice, particularly with respect to certified land rights and state-owned assets that may be deemed abandoned land, thereby resulting in the loss or extinguishment of rights where such land is not effectively utilized. Furthermore, this study proposes an ideal reconstruction of the regulatory framework to ensure legal certainty, justice, and utility in accordance with progressive agrarian law principles that reflect the needs and interests of society. Given that land regulation constitutes a fundamental aspect of both public welfare and state governance, the establishment of an effective, equitable, and legally certain land management regime is indispensable to achieving sustainable national development and the optimal utilization of land resources